Evolutionary trends in Iridaceae: new cytogenetic findings from the New World. (30th December 2014) - Moraes, Ana Paula; Souza‐Chies, Tatiana T.; Stiehl‐Alves, Eudes M.; Burchardt, Paula; Eggers, Lilian; Siljak‐Yakovlev, Sonja; Brown, Spencer C.; Chauveau, Olivier; Nadot, Sophie; Bourge, Mickaël; Viccini, Lyderson Facio; Kaltchuk‐Santos, Eliane
<x xml:space="preserve">Abstract</x> With the present work, we aim to provide a better understanding of chromosome evolutionary trends among southern Brazilian species of Iridoideae. Chromosome numbers and genome sizes were determined for 21 and 22 species belonging to eight genera of Tigridieae and two genera of Trimezieae, respectively. The chromosome numbers of nine species belonging to five genera are reported here for the first time. Analyses of meiotic behaviour, tetrad normality and pollen viability in 14 species revealed regular meiosis and high meiotic indexes and pollen viability (> 90%). The chromosome data obtained here and compiled from the literature were plotted onto a phylogenetic framework to identify major events of chromosome rearrangements across the phylogenetic tree of Iridoideae. Following this approach, we propose that the ancestral base chromosome number for Iridoideae is x = 8 and that polyploidy and dysploidy events have occurred throughout evolution. Despite the variation in chromosome numbers observed in Tigridieae and Trimezieae, for these two tribes our data provide support for an ancestral base number of x = 7, largely conserved in Tigridieae, but a polyploidy event may have occurred prior to the diversification of Trimezieae, giving rise to a base number of x2 = 14 (detected by maximum‐parsimony using haploid number and maximum likelihood). In Tigridieae, polyploid cytotypes were commonly observed (2x, 4x, 6x and 8x), whereas in Trimezieae, dysploidy seems to have been the most important event. This feature is reflected in the genome size, which varied greatly among species of Iridoideae, 4.2‐fold in Tigridieae and 1.5‐fold in Trimezieae. Although no clear difference was observed among the genome sizes of Tigridieae and Trimezieae, an important distinction was observed between these two tribes and Sisyrinchieae, with the latter possessing the smallest genome sizes in Iridoideae. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 177, 27–49.